Xenotransplantation of Human Spermatogonia Into Various Mouse Recipient Models - Liang, Dongli; Sun, Qi; Zhu, Zijue; Wang, Chuanyun; Ye, Shicheng; Li, Zheng; Wang, Yuan (Frontiers in Cell and Developmental Biology, 2022)
Spermatogonial stem cells (SSCs) are the foundation of continuous spermatogenesis in adult mammals. Xenograft models have been established to define human SSCs, mostly using infertile and immune-deficient mice as the recipients for human germ cell transplantation. However, it is time-consuming to prepare such recipients using irradiation or chemotherapeutic agents, and this approach may also introduce confounding factors when residual endogenous germ cells recover in transplanted recipients. It remains to be determined whether immune-competent genetically infertile mice can be suitable recipients for xenotransplantation. In this study, we observed similar engraftment efficiencies when using spermatogonia from human biopsied testes across immune-deficient nude mice, immune-competent ICR mice, and genetically infertile Kitw/w-v mice, suggesting minimal immunological rejection from immune-competent mouse recipients upon xenotransplantation of human germ cells. More importantly, we derived EpCAM negative and TNAP positive spermatogonia-like cells (SLCs) from human pluripotent stem cells (PSCs), which highly expressed spermatogonial markers including PLZF, INTERGRINα6, TKTL1, CD90, and DRMT3. We found that upon transplantation, these SLCs proliferated and colonized at the basal membrane of seminiferous tubules in testes of both immune-deficient nude mice and Kitw/w-v mice, though complete spermatogenesis would likely require supporting human signaling factors and microenvironment. Taken together, our study functionally defined the cell identity of PSC-derived SLCs, and supported xenotransplantation using genetically infertile recipients as a convenient model for functionally evaluating spermatogonia derived from different species.